1998
DOI: 10.1097/00003246-199808000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the sampling site for measurement of mixed venous oxgen saturation in shock

Abstract: These wide range differences and confidence limits would lead to large errors if superior vena cava or right atrial oxyhemoglobin saturations were substituted for true mixed venous blood in oxygen transport or pulmonary venous admixture calculations, or if clinical decision making was based on individual results. In patients in shock in whom clinical decisions may be based on the value of mixed venous oxyhemoglobin, oxyhemoglobin saturation is only reliably measured in samples taken from the pulmonary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 18 publications
0
38
0
7
Order By: Relevance
“…16 O 2 saturation in atrial blood and in the superior vena cava differs from that in mixed blood. This is due to the fact that oxygen consumption varies in the different organs, with greater oxygen consumption in the brain and lower oxygen consumption in the kidneys out of proportion with its flow in blood, causing O 2 saturation to be lower in the superior vena cava than in the inferior vena cava.…”
Section: Figure 4 -mentioning
confidence: 82%
“…16 O 2 saturation in atrial blood and in the superior vena cava differs from that in mixed blood. This is due to the fact that oxygen consumption varies in the different organs, with greater oxygen consumption in the brain and lower oxygen consumption in the kidneys out of proportion with its flow in blood, causing O 2 saturation to be lower in the superior vena cava than in the inferior vena cava.…”
Section: Figure 4 -mentioning
confidence: 82%
“…Reinhart et al have shown that ScvO 2 has a good correlation with SvO 2 [86]. However, there is still debate regarding the equivalence between these two values [87][88][89][90] especially when they are low [91]. The surviving Sepsis Campaign recognized the clinical importance of ScvO 2 and recommended to keep ScvO 2 more than 70 % during the resuscitation of septic shock patients.…”
Section: Scvomentioning
confidence: 99%
“…Lee and co-workers described similar findings (51). Other more detailed studies in mixed groups of critically-ill patients designed to test if the ScvO2 measurements could substitute the SvO2 showed problematically large confidence limits (52) and poor correlation between the two values (53). The hypothesis that slower skeletal muscle StO2 deoxygenation rate (more disturbed tissue oxygen extraction) is proportional to the ScvO2-SvO2 difference in patients with severe heart failure with additional sepsis/septic shock was confirmed (54).…”
Section: Nirs For Evaluation Of Skeletal Muscle Tissue Oxygenation Inmentioning
confidence: 73%